GERAKAN TRANSNASIONAL ISLAM DAN GLOBALISASI SALAFI DI ISLAMIC CENTER BIN BAZ YOGYAKARTA - Abd. Rachman Assegaf (Millah: Journal of Religious Studies, 2017)
This study tries to elaborate critically the globalized Salafi and its transnational movement with specific cases in Islamic Center Bin Baz (ICBB) of Yogyakarta. It focuses on how the institute modernized their education and propagation (dakwa) movements within global contexts. Its roles in globalized Salafi and persisted core values are inherent in the middle of globalization impacts. The research method applied in this study is cultural studies and field studies with data collection techniques of triangularily taken from documentation, interview and observasion. ICBB Yogyakarta, to some extend, applied modern information and communication technology to introduce and draw attention to transnational Islam. From inception, transnational linkage between ICBB and the Middle Eastern education, especially Makkah and Madinah ulamas and universities, had been linked since the establishment of the institute. Some ICBB’s students are come from surrounding villagers but the others from foreign countries such as Thailand, Singapore and Malaysia. On the other hand, Islamic traditional cultures, values and tenets are also manifested in daily life of whole pesantren communities in spite of modernization and globalization influences. Identities, like the way of live, clothes, foods and beverages, and ethical behaviors of these Salafi movements could easily be typically recognized, whereas that performance indicated the persistence of its values towards globalization and modernization. ICBB Yogyakarta represents adaptive position towards global changes and not anti-Government stands or involves directly in practical politics. This study intentionally elaborates the origins and pattern of globalized salafi at ICBB.